LIPID-BASED VEHICLE FOR ORAL DRUG DELIVERY - Stuchlik, Milan; Zak, Stanislav (Biomedical papers, 2001)
With an increasing number of lipophilic drugs under development, homolipids and heterolipids have gainedrenewed interests as excipients for oral drug delivery systems. Oral administration has many advantages for chronicdrug therapy. It is relatively safe, convenient for the patient and allows self administration.This article is notintended to review the broad area of lipid-based vehicle for oral drug delivery comprehensively. The rationalebehind choosing lipids materials for pharmaceutical dosage forms and their applications is discussed. It alsocomments on the methods for monitoring the physicochemical properties of vehicles and formulations anddescribes a range of pharmacopoeial excipients suitable for these purposes. The excipients selected here arepharmacopoeial in European Pharmacopoeia 4th Ed.,United States Pharmacopoeia 24th Ed./National Formulary19th Ed. and Japanese Pharmacopoeia 13th Ed. or are drafted in Pharmaeuropa and Pharmacopoeial Forum.Widening availability of lipidic excipients with specific characteristics offer flexibility of application with respectto improving the bioavailability of poorly water-soluble drugs and manipulating release profiles.
Keywords: Lipids / Lipophilic drugs / Oral drug delivery systems